PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP KARAKTER KREATIF SISWA KELAS 5 PADA MATA PELAJARAN IPA DI SDIT AL-MADINAH CIBINONG - Maryati Maryati; Retno Triwoelandari; Hilman Hakiem (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2018)
The aim of this research is to know the process of applying inquiry model to the crative character of 5th grade students in science subjects in SDIT Al-Madinah Cibinong, and to know the influence of inquiry learning model on the creative character of 5th grade students in science subjects in SDIT Al-Madinah Cibinong. The approach used in this study is quantitative research with the type of quasi-experimental research, in this study the selection of samples on experimental quasi type Non Equivalent Control Group Design is not done random sample selection but deliberately selected by the researchers with each sample experiment class 21 Students and control class of 21 students. The instruments used in this research are: test, observation, questionnaire and documentation. The process of applying inquiry learning model in science subjects through six stages: Presenting questions or problems, Making hypotheses, Designing experiments, Conducting experiments to obtain information, Collecting data and analyzing data, and Making conclusions. Based on the research that has been done, the average post-test of the experimental class is 77.61 and the average post-test of the control class is 64.28 so that it is obtained -t arithmetic> -t table (-11.004> -2.086), it can It is concluded that there is a significant influence of the use of inquiry learning model on student learning outcomes. Observational data resulted in average after applying experimental class learning 92,14, and average after applying of control class study 73,57 so that obtained-t arithmetic> -t table (-20,254> -2,086), hence can be concluded that there is A significant influence of the use of inquiry learning model to foster the creative character of the students. In addition the results of the experimental class questionnaire obtained an average of 32.38 and control classes 31.43 the number of scores in the range 30-36 that students in the experimental class and control classes have a high creative value in carrying out its duties. So it can be concluded that the influence of inquiry learning model to the creative character of students. So the application of inquiry learning model can influence the students' creative character in science subjects are said to be effective and there are significant changes or improvements. This inquiry learning model can be an alternative learning model that can be applied in the learning process.